A Study on Acid Hydrolysis and Composition of Polysaccharides Concentrated from Coconut Kernel - Yalegama, Loku Liyana Waduge Chandi; Karunaratne, Desiree Nedra; Sivakanesan, Ramaiah (International Coconut Community, 2022)
Defatted dehydrated coconut kernel powder (DDCP) is the by-product obtained from virgin coconut oil production through dry process. The aim of the study was to concentrate polysaccharides from DDCP and to investigate their acid hydrolysis capacity and the monosaccharides composition. Residual fat, protein and soluble sugars of DDCP were removed to concentrate coconut kernel Insoluble polysaccharides (CKIP) while water extract of DDCP was used to concentrate coconut kernel soluble polysaccharides (CKSP). Neutral detergent solution (NDS) was used to concentrate neutral detergent soluble polysaccharides (NDSP) and neutral detergent insoluble polysaccharides (NDIP) from CKIP. The acid detergent solution (ADS) was used to concentrate acid detergent soluble polysaccharides (ADSP) and acid detergent insoluble polysaccharides (ADIP) from CKIP. Results indicated fresh coconut kernel contained 7.2±1.5% carbohydrates and the content increased to 78.1±1.3% with the removal of residual fat, protein and sugars. The yields of the polysaccharide fractions were 46.0±3.1% (CKIP) and 9.2± 0.1% (CKSP), 10.2±0.3% (NDSP) and 78.3±4.2% (NDIP), 25.1±0.3% (ADSP) and 45.2±2.9% (ADIP). Trifluoracetic acid had a higher hydrolyzing capacity than sulphuric acid except for hydrolyzing of ADIP. The monosaccharides composition of the polysaccharides was significantly different (p<0.05) among the polysaccharide concentrates. The main monosaccharides in NDSP were glucose (73.86%) and xylose (19.7%) and, in ADSP were rhamnose (33.45%) and glucose (46.91%). Rhamnose (29.95%) arabinose (26.38%), xylose (21.56%) and mannose (12.87%) were present in CKSP while mannose (68.46%), galactose (20.59%) and xylose (10.59%) were present in CKIP. Results indicated that soluble polysaccharides of coconut kernel were hydrolyzed into monosaccharides readily compared to the insoluble polysaccharides.